Assessing Volatilities of Monetary Policy and their Effects on the Islamic and Conventional Stock Markets in Indonesia - M Shabri Abd Majid (Signifikan: Jurnal Ilmu Ekonomi, 2018)
The main objective of this study is to empirically assess the volatilities of the monetary policy instruments and their effects on the Indonesian Islamic and conventional stock market. The changes in exchange rate, interest rates, and money supply and their effects on the stock markets are investigated using the using the Generalized Autoregressive Conditional Heteroskedasticity frameworks. As a big-open economy, the capital market of Indonesia is vulnerable to the global monetary shocks changes, thus the US federal funds rate is also incorporated into the GARCH model. The study documented that, with the exception of the US interest rate, the volatilities of all monetary policy variables of interest rate, exchange rate, and money supply were documented affecting the volatilities of both Islamic and conventional stock markets. These findings imply that the volatilities of Islamic and conventional stock markets have similar determinants, thus to stabilize the markets, the investigated monetary policy variables should be controlled for by the policy-makers. Any monetary policy design imposed by the policy-makers would have a similar effect on both conventional and Islamic stocks in Indonesia.DOI: 10.15408/sjie.v7i2.7352